Śrīvidyāntargatā saptamī Dhūmāvatī mahāvidyā: 'Jñāna'-'Saparyā' khaṇḍātmikā - Prahlāda Giri, Gosvāmĩ ca. 20./21.Jh. (Bitthaldas Sanskrit series, 2017)
Hindu tantric text dealing with the rituals, tantra and mantra of Dhūmavatī, 7th form of Śakti, Hindu diety